1985
DOI: 10.1139/m85-115
|View full text |Cite
|
Sign up to set email alerts
|

Production of the reserve material poly-β-hydroxybutyrate and its function in Azospirillum brasilense Cd

Abstract: Azospirillum brasilense Cd was grown in ammonium–malate mineral salts medium in batch culture and in chemostat continuous culture. It was found that poly-β-hydroxybutyrate synthesis was favored under oxygen limitation in chemostat culture and under high C/N ratios towards the end of exponential growth in batch culture. The degradation and synthesis of poly-β-hydroxybutyrate under starvation conditions occurred in a biphasic pattern and was affected by the poly-β-hydroxybutyrate content of the cells. During a 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 0 publications
6
75
0
1
Order By: Relevance
“…Azospirillum brasilense Cd (ATCC 29729) was grown at 30 "C in ammonia/malate mineral salts medium containing a limiting amount of ammonia (2.8 m-NH,Cl) in order to favour PHB production and BOHB-DH activity (Tal & Okon, 1985). Bacterial cells were collected from 36 h cultures by centrifugation at 5OOO g and washed twice in 0.2 M-potassium phosphate buffer pH 8-0 + 1 mM-MgC1,.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Azospirillum brasilense Cd (ATCC 29729) was grown at 30 "C in ammonia/malate mineral salts medium containing a limiting amount of ammonia (2.8 m-NH,Cl) in order to favour PHB production and BOHB-DH activity (Tal & Okon, 1985). Bacterial cells were collected from 36 h cultures by centrifugation at 5OOO g and washed twice in 0.2 M-potassium phosphate buffer pH 8-0 + 1 mM-MgC1,.…”
Section: Methodsmentioning
confidence: 99%
“…PHB degradation and its utilization as sole carbon and energy source by A . brasilense may be involved in favouring establishment, proliferation, survival and competition with other organisms in the rhimsphere (Tal & Okon, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…According to Tal and Okon (1985), the synthesis of PHB is favored under oxygen limitation and by the C:N ratio of the culture medium. In a study by Belal (2013), the best C:N ratio for the PHB production by Rhizobium etli E1 and Pseudomonas stutzeri E114 was 20:1.…”
Section: Cell Dry Weight Accumulation and Accumulation Of Polyhydroxymentioning
confidence: 99%
“…Cell viability can also be improved by the synthesis of polyhydroxybutyrate (PHB), a reserve polymer that allows bacteria to withstand environmental stresses (Tal and Okon, 1985;Kadouri et al, 2003;Bhat and Subin, 2015). Kadouri et al (2003) observed that the synthesis and use of PHB as carbon and energy sources by A. brasilense strain Sp7 favored the establishment of this bacterium and its survival in competitive environments under stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…PHAs are biopolymers that are beneficial to bacteria and environment; they are utilized as nutrient under stressful condition in rhizosphere, soil, and phyllosphere [175,179,[180][181][182][183], distribution of carbon sources [184][185][186][187], enhancing survival factors in stress condition; osmotic shock, solvent stress, UV irradiation, heat and cold, ethanol, H2O2, and desiccation [188][189][190][191][192][193]183,[194][195][196] and control exopolysaccharide production [197,198,191,192,199] play a vital role in different energy consuming pathways, chemotaxis, nitrogen fixation, cell motility and aerotaxis [200,51,183,201,202], formation of cyst, germination, and sporulation [203]. Despite the PAHs producing significant advances, bacterial inoculants currently received much attention in plant growth promotion or plant production [204].…”
Section: Need For Phas For Microorganismsmentioning
confidence: 99%